Isolation, purification, and characterization of bioactive peptide from Chenopodium quinoa seeds: therapeutic and functional insights - Sen, Amit; Sharma, Gunjan; Tomer, Nalini; Shibu B., Sahaya; Moin, Sarmad (Journal of Applied Pharmaceutical Research, 2024)
Background: Chenopodium quinoa is a nutrient-dense pseudocereal packed with proteins, vital amino acids, and bioactive substances that may have medicinal uses. These include antioxidant, anti-inflammatory, anti-cancer, and antibacterial properties. Notably, quinoa proteins and peptides show multifunctional bioactivities such as immunological regulation, cancer cell death, and microbial suppression. This study aimed to separate, purify, and describe the bioactive proteins found in quinoa seeds, emphasizing their potential applications as medicines. Methodology: Quinoa seeds underwent protein extraction, defatting, and de-saponification. Ion exchange chromatography, dialysis, and ammonium sulfate precipitation were used to purify the seeds. The Lowry technique was used to quantify the proteins. Functional tests assessed the seeds' antibacterial, antifungal, protease, and anticancer properties, and peptide identification was carried out using LC-MS/MS. Results: The protein content decreased during purification steps, indicating effective removal of impurities. Protein fractions exhibited significant antibacterial and antifungal activities. Protease activity varied among fractions, with the pH 2 fraction showing the highest activity. Crude extract and pH 2-treated fractions demonstrated significant anticancer activity against A549 and Hela cell lines. pH 2 fraction exhibits the highest protease activity of 2.451 units/ml, indicating enhanced enzymatic capability under acidic conditions. Peptides identified from the pH 2 fraction showed potential therapeutic properties. Conclusion: The antibacterial, antifungal, proteolytic, and anticancer properties of quinoa-derived peptides and proteins demonstrate their potential for use in medicine. Clinical validation and the creation of functional foods or nutraceuticals based on quinoa should be the main objectives of future research.